2014
DOI: 10.1097/wnp.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Profile in Opioid Dependence

Abstract: Use of opioids cause sleep disturbance, and these changes occurring in sleep can persist even after substance use has been stopped. Opioids seem to affect non-rapid eye movement stages of sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our results showed that an earlier age at the onset of heroin exposure predicted the subsequent onset of CPSD. Although a previous study demonstrated no association between the age at onset of heroin use and sleep disturbance, 39 it has also been reported that patients with long-term opioid use frequently have severe sleep-disordered breathing, which in part is central in origin. 40 , 41 Furthermore, a longer duration of MMT has been significantly correlated with obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 82%
“…Our results showed that an earlier age at the onset of heroin exposure predicted the subsequent onset of CPSD. Although a previous study demonstrated no association between the age at onset of heroin use and sleep disturbance, 39 it has also been reported that patients with long-term opioid use frequently have severe sleep-disordered breathing, which in part is central in origin. 40 , 41 Furthermore, a longer duration of MMT has been significantly correlated with obstructive sleep apnea.…”
Section: Discussionmentioning
confidence: 82%
“…Previously, reductions in total sleep time were found in patients withdrawing from non-prescription opioids (Hartwell et al, 2014). Mehtry et al in a case-control study documented that opioid-dependent patients experienced decreases in total sleep time after one week of abstinence (Mehtry, Nizamie, Parvez, & Pradhan, 2014). In could be concluded that abstinence might not worsen opioid craving but did reduce total sleep time.…”
Section: Discussionmentioning
confidence: 96%